Perhitungan Break Even Point Untuk Mengetahui Profitabilitas Obyek Wisata Pantai Menganti Kebumen - Blandina Hendrawardhani; Sotya Partiwi Ediwijoyo (Politeknik Piksi Ganesha Indonesia, 2022)
This study aimed to determine the profitability of Menganti beach attractions by using the break even point calculation.The data used is the financial statements for the last 3 years, since 2016 till 2018. This research method is quantitative descriptive method. Based on the break-even point calculation, obtained in 2016 was Rp 1,006,478,239 in 2017 Rp. 2,745,476,628 and in 2018 it was Rp 6,754,640,571 so it can be said that the management of tourism objects will break even at the value that. The results of the calculation average on Net Profit Margin (NPM) of 10.03%, are still considered less based on industry profitability standards. To increase visitor interest, the manager of Menganti Kebumen beach tourism object must be able to develop facilities and infrastructure as well as facilities and is expected to further increase revenue volume through promotion.